The Effect Of Drying Method On The Yield Of Kecombrang Leaves (Etilngera Elatoir) Using The Maceration Method With 70% Ethanol Solvent - Tuti Alawiyah; Dwi Yuliani (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Kecombrang leaves (Etlingera elatior) have potential as traditional medicinal materials due to their secondary metabolite content, which exhibits antioxidant and antibacterial activities. Drying is an important step in the processing of plant simplicia. This study aimed to determine the effect of different drying methods (sun drying, drying cabinet, and shade drying/room temperature) on moisture loss and extract yield of kecombrang leaves using the maceration method with 70% ethanol as the solvent. This study employed a completely randomized design with 18 samples. The simplicia were dried according to each method, macerated for 3 days, filtered, and concentrated using a water bath. Data were analyzed using normality and homogeneity tests, followed by One-Way ANOVA and Post Hoc Tukey HSD. The results showed that all methods met the acceptable moisture loss requirement (<10%), with the lowest values obtained from the drying cabinet method (6.53–8.02%) and the highest from shade drying (9.67–9.99%). The highest extract yield was obtained from the drying cabinet method (12–18%), followed by sun drying (8–16%), while shade drying produced the lowest yield (4–12%). One-Way ANOVA indicated a significant difference among the drying methods (p = 0.001). Post Hoc Tukey HSD showed that the drying cabinet method was significantly different from sun drying (p = 0.031) and shade drying (p = 0.002), while no significant difference was found between sun drying and shade drying (p = 0.411). In conclusion, the drying cabinet method is the most effective method for producing higher extract yield of kecombrang leaves.